Majoon ushba, a polyherbal compound ameliorates rheumatoid arthritis via regulating inflammatory and bone remodeling markers in rats. (January 2016) - Ganesan, Ramamoorthi; Doss, Hari Madhuri; Rasool, Mahaboobkhan
Highlights: Majoon ushba ameliorates adjuvant-induced arthritis in rats. Majoon ushba inhibited the production of pro-inflammatory cytokines. Majoon ushba downregulated the NF-kB, AP-1, and cytokines mRNA expression. It also suppressed the IL-17 and COX-2 protein expression. Majoon ushba effectively regulates RANKL and OPG protein expression. Abstract: The present study was aimed to investigate the anti-arthritic effect of majoon ushba (MU) and its underlying mechanism in adjuvant induced arthritis (AIA) rats. Arthritis was induced by intradermal injection of complete freund's adjuvant (0.1 ml) into the right hind paw of the Wistar albino rats. MU (1000 mg/kg/b. wt) and methotrexate (3 mg/kg/b. wt) were administered from day 11 to day 18th for 8 days after adjuvant induction. We have found that MU treatment significantly increased the level of anti-inflammatory cytokine (IL-10) and inhibited the over production of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) and monocyte chemoattractant protein-1 (MCP-1) (ELISA) in the serum of adjuvant-induced arthritic rats. The mRNA expression of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-17), inflammatory enzymes (inducible nitric oxide synthase (iNOS) and cyclo-oxygenase-2 (COX-2)), MCP-1, receptor activator of nuclear factor-kB ligand (RANKL) and transcription factors (NF-кB and AP-1) (Real-Time PCR) was found significantly downregulated in the synovial tissues of MU treated arthritic rats. In addition, the protein expression of NF-кB, IL-17, COX-2, and RANKL (western blotting and immunohistochemistry analysis) was found reduced. On the other hand, osteoprotegerin (OPG), a bone remodeling marker was found to be elevated in synovial tissues of MU treated arthritic rats. Furthermore, MU treatment prevented body weight loss and reduced the joint paw edema, cell infiltration, cartilage and bone degradation as evidenced by the histopathological and radiological analysis. In conclusion, our current findings provide scientific evidence for the traditional claim of MU as an anti-arthritic drug.